A new phenol glycoside from Physalis angulata. Issue 9 (3rd May 2017) - Sun, Cheng-Peng; Nie, Xiu-Fang; Kang, Ning; Zhao, Feng; Chen, Li-Xia; Qiu, Feng
Abstract: A new phenol glycoside, physanguloside A (1 ), was isolated from Physalis angulata together with four known compounds. We report herein, for the first time, the presence of compounds2 –5 in the genus Physalis . The structures of all the compounds were established by NMR, IR, UV and HRESIMS spectroscopic analyses, and comparison with the literature data. All isolated compounds were assayed for inhibitory activity on nitric oxide production by LPS-induced in RAW 264.7 macrophages. Abstract :